Dietary Phytochemicals in Neuroimmunoaging: A New Therapeutic Possibility for Humans? - Corbi, Graziamaria; Conti, Valeria; Davinelli, Sergio; Scapagnini, Giovanni; Filippelli, Amelia; Ferrara, Nicola (Frontiers in Pharmacology, 2016)
Although several efforts have been made in the search for genetic and epigenetic patterns linked to diseases, a comprehensive explanation of the mechanisms underlying pathological phenotypic plasticity is still far from being clarified. Oxidative stress and inflammation are two of the major triggers of the epigenetic alterations occurring in chronic pathologies, such as neurodegenerative diseases. In fact, over the last decade, remarkable progress has been made to realize that chronic, low-grade inflammation is one of the major risk factor underlying brain ageing. Accumulated data strongly suggest that phytochemicals from fruits, vegetables, herbs, and spices may exert relevant immunomodulatory and/or anti-inflammatory activities in the context of brain aging. Starting by the evidence that a common denominator of aging and chronic degenerative diseases is represented by inflammation, and that several dietary phytochemicals are able to potentially interfere with and regulate the normal function of cells, in particular neuronal components, aim of this review is to summarise recent studies on neuroinflammaging processes and proofs indicating that specific phytochemicals may act as positive modulators of neuroinflammatory events. In addition, critical pathways involved in mediating phytochemicals effects on neuroinflammaging were discussed, exploring the real impact of these compounds in preserving brain health before the onset of symptoms leading to inflammatory neurodegeneration and cognitive decline.